The Determinants and Forecasting of Electricity Consumption in Pakistan - Wahid, Fazle; Ullah, Hamid; Ali, Sher; Jan, Sajjad Ahmad; Ali, Abid; Khan, Azhar; Khan, Imran Ali; Bibi, Maryam (International Journal of Energy Economics and Policy, 2020)
The current study examined the determinants of electricity consumption and also intends to forecast the electricity consumption in Pakistan. The study has used time series data analysis, applied Johansen Cointegration Test, error correction mechanisms and regression for examining determinants and autoregressive integrated moving average model is used for forecasting. The study has used times series secondary annual data on different variables for the period ranging from 1970 to 2018. The results of the study showed that gross domestic product and population have positive impact on electricity consumption. Whereas, National output (GDP) is statistically significant in the determination of total electricity consumption. The results also indicated that increase in the real economic activities has increases the total electricity consumption. Furthermore, the results of electricity consumption model also suggest that electricity price have negative impact on total electricity consumption. As electricity demand is inelastic to electricity price and income, it indicates that fewer substitutes of electricity are available in the market. Hence electricity is essential component of energy for economy. The results of the current study can be useful for the policymakers and government regulatory bodies relating to electricity. Keywords: Determinants, Electricity Consumptions, ARIMA, Pakistan JEL Classifications: G2, M53, Q4 DOI: https://doi.org/10.32479/ijeep.10646